Understanding Family Burden as Caregiver in Stroke Patients: Case Study - Pitri, Angela Dwi; Febryanto, Dwi; Pambudi, Hubertus Agung; Raisa, Raisa (Jurnal Keperawatan Profesional (KEPO), 2025)
A family member who acts as a caregiver is subjected to continuous distress while taking care of a stroke patient due to physical and psychological burdens. Most caregivers in Indonesia, or 47,2%, are young women. Research revealed that 45% of caregivers for stroke survivors experienced depression, and 64% underwent work and financial loads. Caregivers are responsible for feeding, maintaining hygiene, and doing daily activities in their caring. Several studies have focused on the stroke patients’ medical problems, whereas this study attempted to investigate the burden on family members as caregivers. This study employed a qualitative case study approach, utilizing a single-case study design. The data was processed using Colaizzi’s data analysis, which includes reading, identifying significant opinions, formulating meaning, and theming. The results revealed four themes on the caregivers’ burden, namely physical problems, hygiene care, medical care costs, and limited socializing activities. To summarize, physical problems are the main cause of caregivers’ distress, and caregivers are recommended to organize shifting schedules among family members in order to spare more time for their caring or any recreational activities.